Alumina crystallization barrier for hybrid bonding

CN122936039APending Publication Date: 2026-10-16APPLIED MATERIALS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580020096.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-08
Filing Date
2025-03-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,发明人已经观察到,在使用氧化铝的混合接合处理期间,金属互连与触点之间会出现不良接合,导致低的产量

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122936039A_ABST
    Figure CN122936039A_ABST
Patent Text Reader

Abstract

A method for substrate processing for hybrid bonding includes forming an aluminum oxide crystalline barrier on a metal contact. In some embodiments, the method can include providing a substrate to prepare for a hybrid bonding process, where the substrate has an aluminum oxide (AI2O3) bonding layer on an uppermost surface of the substrate, and a metal contact is present in the aluminum oxide bonding layer. A crystalline barrier is formed on an uppermost surface of the metal contact. The crystalline barrier disrupts crystallization of the aluminum oxide bonding layer during a subsequent anneal process of the hybrid bonding process due to interaction of the aluminum oxide material of the aluminum oxide bonding layer and the metal material of the metal contact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The implementation of this principle generally involves semiconductor processing of semiconductor substrates. Background Technology

[0002] Hybrid bonding involves linking or joining more than one type of material. In semiconductor manufacturing, hybrid bonding is used to package components by bonding one substrate or die to another, linking not only dielectric surfaces but also metal interconnects or contacts. Traditionally, dielectrics (such as silicon dioxide) provide most of the bond strength in hybrid bonding. As interconnect and contact density increases, the dielectric material bonding area decreases. To help ensure successful bonding with dies or substrates with high-density contacts, dielectric materials with higher bond strength (such as alumina) can be introduced during the manufacturing process. However, the inventors have observed poor bonding between metal interconnects and contacts during hybrid bonding processes using alumina, resulting in low yields.

[0003] Therefore, the inventors have provided a method for improving the hybrid bonding performance of substrates with an alumina bonding layer. Summary of the Invention

[0004] This paper presents a method for improving hybrid bonding properties by incorporating alumina crystallization barriers.

[0005] In some embodiments, a method for substrate processing may include providing a first substrate for preparation for a hybrid bonding process, forming a hybrid bonding layer on the first substrate, wherein the hybrid bonding layer comprises an alumina (Al2O3) bonding layer on the uppermost surface of the first substrate, metal contacts, and a crystallization barrier on the uppermost surface of the metal contacts, wherein the crystallization barrier disrupts the crystallization of the alumina bonding layer on the metal contacts during the hybrid bonding process.

[0006] In some embodiments, the method may further include: bonding a first substrate to a second substrate via a hybrid bonding layer; a metal contact, which is copper; a crystal barrier formed of a material having a lattice structure different from that of the metal contact; a material, which is ruthenium having a hexagonal close-packed (HCP) lattice structure (lattice constant of 2.7 Å); a crystal barrier formed of a material having a lattice structure similar to that of the metal contact; a material, which is cobalt having a face-centered cubic (FCC) lattice structure (lattice constant of 3.9 Å); a crystal barrier having a single-layer thickness; and a crystal barrier having a thickness greater than zero to approximately 2. A thickness of nm; a crystallization barrier formed using selective atomic layer deposition (ALD); the uppermost surface of the metal contact having a groove located below the uppermost surface of the alumina bonding layer, and the crystallization barrier having a thickness less than the groove, allowing the metal contact to expand during subsequent annealing of the hybrid bonding process; an alumina bonding layer formed on silicon dioxide; and / or an alumina bonding layer formed on silicon carbonitride.

[0007] In some embodiments, a substrate prepared for hybrid bonding includes a dielectric material, a dielectric bonding layer formed on the dielectric material, at least one metal contact, and a crystallization barrier located on the uppermost surface of the metal contact, wherein the uppermost surface of the crystallization barrier is exposed in the dielectric bonding layer, and wherein the crystallization barrier has a lattice structure that disrupts the crystallization of the dielectric bonding layer.

[0008] In some embodiments, the substrate may further include: a dielectric bonding layer, which is an aluminum oxide (Al2O3) layer, wherein at least one of the at least one metal contact is copper; a crystallization barrier formed of a material having a lattice structure different from that of the metal contact; a crystallization barrier formed of a material having a lattice structure similar to that of the metal contact; a crystallization barrier having a single-layer thickness; and / or a substrate and another substrate, which are mixedly bonded to the substrate through the dielectric bonding layer and at least one metal contact.

[0009] In some embodiments, a non-transitory computer-readable medium has instructions stored thereon that, when executed, cause the execution of a method for substrate processing. The method may include providing a substrate in preparation for a hybrid bonding process, forming a hybrid bonding layer on the substrate, wherein the hybrid bonding layer comprises an alumina (Al2O3) bonding layer on the uppermost surface of the substrate, metal contacts, and a crystallization barrier on the uppermost surface of the metal contacts, wherein the crystallization barrier disrupts the crystallization of the alumina bonding layer on the metal contacts during the hybrid bonding process.

[0010] Other and further implementation methods are disclosed below. Attached Figure Description

[0011] The embodiments of this principle, briefly summarized above and discussed in more detail below, can be understood by referring to the illustrative embodiments of the principle shown in the accompanying drawings. However, the drawings only illustrate the general implementation of the principle and should not be considered as a limitation of the scope, as the principle can allow other equally effective embodiments.

[0012] Figure 1 According to some embodiments of this principle, there is a method for preparing a substrate for hybrid bonding.

[0013] Figure 2 According to some embodiments of this principle, a cross-sectional view of a substrate prepared for hybrid bonding processing is shown.

[0014] Figure 3 According to some embodiments of this principle, a cross-sectional view of a substrate in which an alumina crystal barrier is formed on the metal contacts of the substrate is shown.

[0015] Figure 4 According to some embodiments of this principle, a cross-sectional view of a hybrid bonding process for alumina-free crystallization barriers is shown.

[0016] Figure 5 According to some embodiments of this principle, a cross-sectional view is shown using a hybrid bonding process of metal contacts and alumina crystal barriers.

[0017] For ease of understanding, the same reference numerals are used as much as possible to represent the same elements in the figures. The figures are not drawn to scale and may be simplified for clarity. Elements and features of one embodiment may be advantageously incorporated into other embodiments without further description. Detailed Implementation

[0018] This method provides improved hybrid bonding performance by providing an alumina crystal barrier on the uppermost surface of the metal contacts. The alumina crystal barrier prevents the bonding surfaces of the metal contacts from interacting with the alumina during the annealing process associated with the hybrid bonding process, thereby achieving high dielectric strength and contact bond strength. The high bond strength provided by this method enables increased metal contact density, allowing for the scaling of semiconductor devices. This technique can be performed using a selective deposition process to deposit the alumina crystal barrier only on the metal contacts of the substrate, providing a fast and efficient process to prevent metal contact bond failure in hybrid bonding processes using alumina bonding layers.

[0019] Traditional dielectrics, such as silicon dioxide, limit component scaling due to the bonding strength of the dielectric material. To increase metal contact density, the bonding strength of the dielectric used in hybrid bonding must be increased, as the bonding strength of metal contacts is relatively low compared to dielectric bonding strength. Alumina is being considered as an alternative to dielectric materials such as silicon dioxide or silicon carbonitride. Compared to silicon dioxide or silicon carbonitride, alumina offers a 40% to 80% increase in bonding strength. However, the inventors discovered that when substrates with an alumina bonding layer and metal contacts are bonded together and then annealed, alumina migrates to the top surface of the metal contacts and prevents them from bonding. The inventors believe that this migration of alumina is caused by its low-temperature crystallization. Typically, alumina crystallizes at around 850 degrees Celsius. The annealing temperature for hybrid bonding is generally around 350 degrees Celsius. The inventors believe that the crystals of the metal material (e.g., copper) in the metal contacts act as a catalyst for alumina crystallization, thereby lowering the crystallization temperature to or below the annealing temperature. Low temperatures cause alumina to crystallize during the annealing of the bonded substrates and migrate / diffuse on the surface of the metal contacts (e.g., at a given temperature, the diffusion rate of alumina is higher than that of copper, resulting in alumina migration).

[0020] The inventors have discovered that for successful bonding using an alumina bonding layer, alumina crystallization and subsequent migration due to the upper surface or bonding surface of the contact copper contacts should be minimized. In this method, alumina migration during hybrid bonding can be suppressed by providing an alumina crystallization barrier that protects the bonding surface of the metal contacts from interaction with the alumina bonding layer during annealing. The alumina crystallization barrier material can be one that disrupts alumina crystallization by having a different lattice structure from or a similar lattice structure to the metal material of the metal contacts. The inventors have found that alumina crystallization can be disrupted using a thin, monolayer alumina crystallization barrier. In some embodiments, the thickness is limited to less than the depth of the recessed groove to allow the metal contact material to expand during annealing.

[0021] Alumina crystallization barriers inhibit grain nucleation (the site where crystal growth begins) by using elements that disrupt the alumina lattice, thus preventing crystallization at low temperatures (approximately 300°C to approximately 400°C). For example, but not limited to, when copper is used as the metal contact material, alumina crystallization barriers can be formed from specific lattice structure variants of cobalt (similar) or ruthenium (different). Copper has a face-centered cubic (FCC) lattice structure with a lattice constant of 3.61 Å. A lattice structure variant of cobalt can have an FCC lattice structure with a lattice constant of 3.49 Å. The lattice constant value of the cobalt lattice structure variant is close enough to copper to allow the cobalt variant to grow readily on copper, but differs enough from the copper lattice structure to prevent alumina from crystallizing and migrating to the top surface of the metal contact when alumina comes into contact with cobalt (rather than with copper).

[0022] Ruthenium lattice variants can have a hexagonal close-packed (HCP) lattice structure with a lattice constant of 2.76 Å. The ruthenium lattice structure is significantly different from that of copper; therefore, when alumina comes into contact with ruthenium (rather than with copper), the alumina does not crystallize and migrate to the top surface of the metal contact. The conductivity of the alumina crystallization barrier material must also be considered, as it becomes part of the bonded metal contact. If the resistance is not negligible, the alumina crystallization barrier material will affect the performance of the metal contact. If the resistance of the material is greater than that of the underlying metal contact material (contact resistance increases with thickness), the thickness of the alumina crystallization barrier material will also affect the performance of the metal contact.

[0023] Figure 1 This is a method 100 for preparing a substrate 202 for hybrid bonding. In block 102, a substrate is obtained in preparation for a hybrid bonding process, such as... Figure 2 View 200 shows the substrate 202, which may be at least partially formed of a dielectric layer 204, such as, but not limited to, silicon dioxide or silicon carbonitride dielectric materials. In some embodiments, the substrate 202 may undergo prior device fabrication and / or packaging processes to prepare the substrate 202 for bonding to another substrate and / or die. The substrate 202 has an alumina bonding layer 206 with metal contacts 210. The alumina bonding layer 206 may have a thickness 234 of about 30 nm to about 50 nm. In some embodiments, the substrate 202 may undergo chemical mechanical planarization (CMP) to remove portions of the alumina bonding layer 206 and / or form recesses or grooves 230 on the uppermost surface 212 of the metal contacts 210 below the uppermost surface 208 of the alumina bonding layer 206. In some embodiments, the grooves 230 may have a depth 214 of about 5 nm to about 10 nm. The groove 230 allows the metal material of the metal contact 210 to expand during the annealing process of the mixed bonding process and bond with the metal contact on another substrate or die.

[0024] In frame 104, an alumina crystal barrier 216 is formed on the uppermost surface 212 of the metal contact 210, such as Figure 3View 300 shows the deposition of the alumina crystal barrier 216. The deposition can be accomplished using any type of selective deposition process compatible with the back-end production line (BEOL) substrate and thermal budget (typically 400 degrees or lower). The thickness 232 of the alumina crystal barrier 216 can range from a single layer to approximately 2 nm. In some embodiments, the thickness 232 is a single layer and is deposited using atomic layer deposition (ALD). The thickness 232 of the alumina crystal barrier 216 has a negligible effect on the amount of expansion of the metal material of the metal contact 210 during annealing and subsequent volume changes. The alumina crystal barrier 216 does not affect the annealing temperature of the hybrid bonding process. The depth 218 of the groove 230 after the formation of the alumina crystal barrier 216 is less than the depth 214 of the groove 230 before the deposition of the alumina crystal barrier 216. The depth 218 is still sufficient to allow the metal contact 210 to expand during the annealing process of the hybrid bonding process. In some embodiments, the depth 218 can range from about 3 nm to about 5 nm or more, depending on the thickness 232 of the alumina crystal barrier 216. The alumina bonding layer 206, the metal contact 210, and the alumina crystal barrier 216 form a hybrid bonding layer on the substrate 202.

[0025] In frame 106, a hybrid bonding process is performed on substrate 202 to bond substrate 202 to another substrate or die (see [link]). Figure 5 (and described below). The hybrid bonding process includes first bonding dielectric materials together by bringing the alumina bonding layer 206 into contact with another alumina bonding layer. When the dielectric materials come into contact, they are bonded together. In some embodiments, the hybrid bonding process may also include adding additional force to press the dielectric materials together. After the dielectric materials are bonded, the metal contacts 210 remain unbonded. Bonding of the metal contacts requires heat to expand the metal of the metal contacts, causing the metal contacts to bond together. The annealing process of the hybrid bonding process is performed at a temperature of about 300 degrees Celsius to about 400 degrees Celsius. As the metal material of the metal contacts expands, the alumina crystallization barrier 216 comes into contact with another alumina crystallization barrier of another metal contact on another substrate, thereby bonding the metal contacts together. The alumina crystallization barrier 216 prevents the alumina material of the alumina bonding layer 206 from contacting the underlying metal material of the metal contact 210, thereby preventing alumina from crystallizing and migrating on the uppermost surface 212 of the metal contact 210.

[0026] The above methods can be used to enhance the bonding strength and yield of hybrid bonding processes. For example, such as... Figure 4As shown in view 400A, substrates 402A and 402B can be bonded together. Substrates 402A and 402B have silicon layers 404A and 404B, silicon dioxide layers 406A and 406B (or silicon carbonitride layers, etc.), and metal contacts 408A and 408B. The bonding layers are aluminum oxide bonding layers 410A and 410B. Figure 4 As shown in view 400B, when substrates 402A and 402B having alumina bonding layers 410A and 410B come into contact (bond) with each other, the alumina bonding layers 410A and 410B form a single alumina bonding layer 410. Metal contacts 408A and 408B are not yet bonded together, and a gap 412 exists between metal contacts 408A and 408B due to the formation of grooves on each metal contact during CMP processing. To close the gap 412 and form continuous contacts, substrates 402A and 402B undergo annealing at temperatures up to approximately 400 degrees Celsius. The inventors discovered that during annealing, the alumina material of the alumina bonding layers crystallizes at a significantly lower temperature (approximately 400 degrees Celsius or lower compared to the normal crystallization temperature of approximately 850 degrees Celsius) because the material of the metal contacts (e.g., copper, etc.) acts as a crystallization catalyst. Figure 4 As shown in view 400C, the significantly reduced crystallization temperature allows the individual alumina bonding layer 410 to crystallize and migrate to the surfaces 414A, 414B of the metal contacts 408A, 408B during the annealing process, thereby preventing the metal contacts 408A, 408B from bonding together.

[0027] like Figure 5 As shown in view 500A, substrates 502A and 502B can be bonded together using the method described above. In some embodiments, substrates 502A and 502B may include dielectric layers, such as, but not limited to, silicon dioxide and / or silicon carbonitride. In an example, substrates 502A and 502B have silicon layers 504A and 504B, silicon dioxide layers 506A and 506B (or silicon carbonitride layers, etc.), and metal contacts 508A and 508B. The bonding layers are alumina bonding layers 510A and 510B. Metal contacts 508A and 508B have alumina crystal barriers 520A and 520B on their uppermost parts or bonding surfaces. Figure 5 As shown in view 500B, when substrates 502A and 502B are in contact (bonded), alumina bonding layers 510A and 510B form a single alumina bonding layer 510. Metal contacts 508A and 508B are not yet bonded together, and a gap 512 exists between metal contacts 508A and 508B due to grooves formed on each metal contact during CMP processing.

[0028] To close the gap 512 and form a continuous contact, substrates 502A and 502B require annealing at temperatures as high as approximately 400 degrees Celsius. The inventors discovered that by forming alumina crystallization barriers 520A and 520B on the metal contacts 508A and 508B prior to annealing, the alumina material does not crystallize at lower annealing temperatures (approximately 300 to 400 degrees Celsius). Figure 5 As shown in view 500C, the individual alumina bonding layer 510 does not crystallize and migrate to the surfaces 514A, 514B of the metal contacts 508A, 508B during the annealing process, thereby causing the metal contacts 508A, 508B to expand, and the alumina crystallization barriers 520A, 520B bond together to form an individual alumina crystallization barrier 514 and a bonding contact 508.

[0029] Implementations based on this principle can be carried out in hardware, firmware, software, or any combination thereof. Implementations can also be implemented as instructions stored using one or more computer-readable media, which can be read and executed by one or more processors. The computer-readable media can include any mechanism for storing or transmitting information in a machine-readable form (e.g., a computing platform or a “virtual machine” running on one or more computing platforms). For example, the computer-readable media can include any suitable form of volatile or non-volatile memory. In some implementations, the computer-readable media can include non-transitory computer-readable media.

[0030] Although the foregoing describes an implementation of this principle, other and further implementations of this principle can be designed without departing from its basic scope.

Claims

1. A method for processing a substrate, the method comprising: A first substrate is provided in preparation for hybrid bonding processing; A hybrid bonding layer is formed on the first substrate, the hybrid bonding layer comprising the following: An aluminum oxide (Al2O3) bonding layer on the uppermost surface of the first substrate; Metal contacts; as well as Crystallization barrier on the uppermost surface of the metal contact, wherein the crystallization barrier disrupts the crystallization of the alumina bonding layer on the metal contact during the hybrid bonding process.

2. The method of claim 1, further comprising: The first substrate is mixed and bonded to the second substrate through the hybrid bonding layer.

3. The method of claim 1, wherein the metal contact is copper.

4. The method of claim 1, wherein the crystallization barrier is formed of a material having a lattice structure different from that of the metal contact.

5. The method of claim 4, wherein the material is ruthenium having a hexagonal close-packed (HCP) lattice structure and a lattice constant of 2.7 Å.

6. The method of claim 1, wherein the crystallization barrier is formed of a material having a lattice structure similar to that of the metal contact.

7. The method of claim 6, wherein the material is cobalt having a face-centered cubic (FCC) lattice structure and a lattice constant of 3.9 Å.

8. The method of claim 1, wherein the crystallization barrier has a single-layer thickness.

9. The method of claim 1, wherein the crystallization barrier has a thickness greater than zero to about 2 nm.

10. The method of claim 1, wherein the crystallization barrier is formed using selective atomic layer deposition (ALD).

11. The method of claim 1, wherein the uppermost surface of the metal contact has a groove located below the uppermost surface of the alumina bonding layer, and wherein the crystallization barrier has a thickness less than the groove, such that the metal contact can expand during a subsequent annealing process of the hybrid bonding process.

12. The method of claim 1, wherein the alumina bonding layer is formed on silicon dioxide.

13. The method of claim 1, wherein the alumina bonding layer is formed on silicon carbonitride.

14. A substrate prepared for hybrid bonding, the substrate comprising: Dielectric materials; A dielectric bonding layer is formed on the dielectric material; At least one metal contact; and A crystallization barrier is provided on the uppermost surface of the metal contact, wherein the uppermost surface of the crystallization barrier is exposed in the dielectric bonding layer, and wherein the crystallization barrier has a lattice structure that disrupts the crystallization of the dielectric bonding layer.

15. The substrate of claim 14, wherein the dielectric bonding layer is an aluminum oxide (Al2O3) layer, and wherein at least one of the at least one metal contact is copper.

16. The substrate of claim 14, wherein the crystal barrier is formed of a material having a lattice structure different from that of the metal contacts.

17. The substrate of claim 14, wherein the crystallization barrier is formed of a material having a lattice structure similar to that of the metal contacts.

18. The substrate of claim 14, wherein the crystal barrier has a single-layer thickness.

19. An element comprising: The substrate as claimed in claim 14; and Another substrate is bonded to the substrate via the dielectric bonding layer and the at least one metal contact.

20. A non-transitory computer-readable medium having instructions stored thereon, which, when executed, cause the execution of a method for substrate processing, the method comprising: Provide a substrate in preparation for hybrid bonding processing; A hybrid bonding layer is formed on the substrate, the hybrid bonding layer comprising the following: An aluminum oxide (Al2O3) bonding layer on the uppermost surface of the substrate; Metal contacts; as well as Crystallization barrier on the uppermost surface of the metal contact, wherein the crystallization barrier disrupts the crystallization of the alumina bonding layer on the metal contact during the hybrid bonding process.